2021
DOI: 10.28991/cej-2021-03091752
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil-Structure Interaction on the Seismic Response of the Structure on Mat Foundation

Abstract: The disasters that occur due to seismic activities not only affect the structure but also soil beneath it. Neglecting the effect of Soil-Structure Interaction (SSI) in design leads to unsafe design. This paper focuses on the behavior of the structure under El-Centro earthquake considering soil-structure interaction (SSI). Seismic response of G+10 storied building in various seismic zones of India is obtained using Time-history method. The direct approach i.e., finite element analysis is used to analyze effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Further, it is found that SSI raises ductility demand in the lower levels of a building while decreasing it in the top stories, with these impacts being more obvious in taller buildings. Similar conclusions were also drawn by (Awchat and Monde, 2021). Regarding SSI effects on deep foundations (Visuvasam and Chandrasekaran, 2019) highlighted that the detrimental consequences of SSI are also existing for pile-raft foundation system structures.…”
Section: Moment Resisting Frame Structures Mrfssupporting
confidence: 67%
“…Further, it is found that SSI raises ductility demand in the lower levels of a building while decreasing it in the top stories, with these impacts being more obvious in taller buildings. Similar conclusions were also drawn by (Awchat and Monde, 2021). Regarding SSI effects on deep foundations (Visuvasam and Chandrasekaran, 2019) highlighted that the detrimental consequences of SSI are also existing for pile-raft foundation system structures.…”
Section: Moment Resisting Frame Structures Mrfssupporting
confidence: 67%
“…Similarly, Chore found an increase in lateral displacement when the SSI effect was taken into account [26]. Awchat and Monde found that the lateral storey drift increases by 47-87% in seismic zone II and 60-95% in seismic zone III, IV and V considering SSI [27]. Also, by an increase in gap distance, lateral displacement was reduced.…”
Section: Lateral Roof Displacementmentioning
confidence: 80%
“…Similar results were found during a study conducted on G+10 buildings in different seismic zones of India. The time period increased considering the SSI effect [27]. For example, there was a 15-25% increase in time period when the SSI effect was considered.…”
Section: Time Periodmentioning
confidence: 99%
“…So, the impact of SSI on the seismic behavior of structures was not given significant consideration until some recent earthquakes revealed the detrimental consequences of SSI in certain conditions [14][15][16]. Several recent studies demonstrated how SSI consideration alters seismic demand and the structural response of a building [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%